Toward An Aproch of Recommender System Based on Trust - Imen GMACH; Samreen JAFRI; Naoufel MAHFOUDH; Lotfi KHRIFISH (Communications of International Proceedings, 2021)
This paper focuses on the state of the art of recommender systems. It presents various technical recommendations mentioned in the literature, primarily the basic content filtering, collaborative filtering and hybrid filtering. It comes to study different recommendation algorithms based on trust. The article also introduces the concept of trust in recommender systems. And it ends with a summary of the various existing approaches by developing the link between trust and recommender systems.
Keywords: Confidence Algorithms; Collaborative Filtering; Information Search; Filtering Approaches; Systems of Recommendations; Trust.